Vaksinasi dan Pemberian Obat Cacing sebagai Upaya untuk Meningkatkan Kesehatan Hewan Ternak - Ikhwanul Azhar (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Like humans, livestock are also very susceptible to various types of diseases, both infectious and non-infectious. Vaccination is one way to prevent certain diseases. The purpose of vaccination is essentially to provide immunity (antibodies) to livestock so that they can fight antigens or microorganisms that cause disease. Vaccination is the administration of antigens to stimulate the immune system to produce specific antibodies against diseases caused by viruses, bacteria, and protozoa. As is known, diseases in livestock are divided into infectious diseases and non-infectious diseases. The purpose of this activity is to provide vaccines and deworming drugs as an effort to improve the health of livestock in Pandan Wangi Village, Jerowaru District, East Lombok Regency. After completing the deworming, do not forget to remind the cattle owners that the administration of this deworming drug is very important in order to prevent cattle from getting worms. Worms usually occur in calves. Deworming is highly recommended if the cattle experience symptoms of worms that are not too severe. In essence, prevention so that cattle are not easily infected with worms is to keep cleaning the cattle pen and cleaning the environment where the cattle are. Because worm disease is zoonotic, it can be transmitted from animal to animal or from animal to human. Transmission can occur through contact with worm eggs in feces or direct contact. Wormxzol-b worming medicine for cattle is used as prevention and treatment of gastrointestinal worm infections caused by roundworms, whipworms, hookworms, and tapeworms, as well as control of giardiasis.